Riesgos psicosociales para la seguridad y salud ocupacional de los trabajadores en la empacadora ‘‘Dole’’ del cantón el Carmen - Tufiño Zambrano, Inguevort Betzabé (2020)
The present investigation was carried out at the DOLE Packing Plant, located in the canton El Carmen-Manabí, with the purpose of evaluating the psychosocial risks that exist within the company for its subsequent intervention. The processes carried out throughout the day were known. For the identification of risks, the INSL methodology of the Navarro Institute of Occupational Health was used, which shows the incidence of each factor within the company through surveys aimed directly at workers, with variables such as: participation, involvement, responsibility; training, information, communication, time management; and finally, group cohesion. Subsequently, an estimation of data concerning the responses of each worker was carried out, weighted by means of a table that according to the instrument used numerically evaluates the qualitative appreciations and the quantitative results. With this, it was evident that in the DOLE packing house the main psychosocial risks are associated with the worker's freedom of expression, lack of communication and lack of confidence when having to decide on the tasks to be performed. In order to improve the work environment and comply with the Ministerial Agreement MDT-2017-0082, based on the results obtained, a minimum plan for the prevention of occupational risks was established, consisting of policies, rules and suggestions to develop an optimal work environment.